Hydrous ferric oxide incorporated diatomite for remediation of arsenic contaminated groundwater - Jang, M.; Min, S.H.; Park, J.K.; Tlachac, E.J. (2007)
Two reactive media zerovalent iron (ZVI, Fisher Fe0) and amorphous hydrous ferric oxide (HFO)-incorporated porous, naturally occurring aluminum silicate diatomite designated as Fe (25)-diatomite]], were tested for batch kinetic, pH-controlled differential column batch reactors (DCBRs), in small- and large-scale column tests (about 50 and 900 mL of bed volume) with groundwater from a hazardous waste site containing high concentrations of arsenic (both organic and inorganic species), as well as other toxic or carcinogenic volatile and semivolatile organic compounds (VOC/SVOCs). Granular activated carbon (GAC) was also included as a reactive media since a permeable reactive barrier (PRB) at the subject site would need to address the hazardous VOC/SVOC contamination as well as arsenic. The groundwater contained an extremely high arsenic concentration (341 mg L-1) and the results of ion chromatography and inductively coupled plasma mass spectrometry (IC-ICP-MS) analysis showed that the dominant arsenic species were arsenite (45.1) and monomethyl arsenic acid (MMAA, 22.7), while dimethyl arsenic acid (DMAA) and arsenate were only 2.4 and 1.3, respectively. Based on these proportions of arsenic species and the initial As-to-Fe molar ratio (0.15 molAs molFe-1), batch kinetic tests revealed that the sorption density (0.076 molAs molFe-1) for Fe (25)-diatomite seems to be less than the expected value (0.086 molAs molFe-1) calculated from the sorption density data reported by Lafferty and Loeppert (Environ. Sci. Technol. 2005, 39, 2120-2127), implying that natural organic matters (NOMs) might play a significant role in reducing arsenic removal efficiency. The results of pH-controlled DCBR tests using different synthetic species of arsenic solution showed that the humic acid inhibited the MMAA removal of Fe (25)-diatomite more than arsenite. The mixed system of GAC and Fe (25)-diatomite increased the arsenic sorption speed to more than that of either individual media alone. This increase might be deduced by the fact that the addition of GAC could enhance arsenic removal performance of Fe (25)-diatomite through removing comparably high portions of NOMs. Small- and large-scale column studies demonstrated that the empty bed contact time (EBCT) significantly affected sorpton capacities at breakthrough (C = 0.5 C 0) for the Fe0/sand (50/50, w/w) mixture, but not for GAC preloaded Fe (25)-diatomite. In the large-scale column tests with actual groundwater conditions, the GAC preloaded Fe (25)-diatomite effectively reduced arsenic to below 50 Î¼g L-1 for 44 days; additionally, most species of VOC/SVOCs were also simultaneously attenuated to levels below detection. Â© 2007 American Chemical Society.